"I Know They Would Kill Me": Abortion Attitudes and Experiences Among Youth Experiencing Homelessness. Issue 8 (November 2020) - Begun, Stephanie; Combs, Katie Massey; Schwan, Kaitlin; Torrie, Michaela; Bender, Kimberly
Pregnancy rates among youth experiencing homelessness are much higher than those of their housed peers, yet limited research exists on this population's abortion experiences. This study examined abortion attitudes, experiences, and decision making through individual interviews with 30 female, male, and gender-fluid youth (ages 18-21 years) experiencing homelessness. Respondents indicated that abortions are common in this population. Many youth also reported they either had, and/or knew of others, who had attempted abortions outside of the formal medical system while experiencing homelessness. Most youth noted that self-inductions resulted from not knowing where or how to access abortions safely, and as many feared stigma, judgment, and violence from family members and serious partners in response to obtaining abortions. Most youth reflected inaccurate perceptions regarding abortion cost, accessibility, and legality. Findings should be considered in developing socially contextualized family planning prevention and outreach efforts among this highly vulnerable youth population.